Perbedaan Tingkat Pengetahuan Tentang Diabetes Melitus Dengan Kadar Gula Darah Sewaktu Pasien DM Tipe 2 - Samintola Dolok Saribu; Winda Trijayanthi Utama (Medula, 2026)
Diabetes mellitus (DM) is a degenerative disease characterized by elevated blood sugar levels or hyperglycemia. The incidence of DM continues to increase every year, influenced by various factors such as suboptimal recovery, the need for continuous consumption of antidiabetic drugs, uncontrolled blood sugar levels, and low patient knowledge about the disease. This condition can worsen complications and reduce the quality of life of patients. This study was conducted to determine the difference in the level of knowledge about diabetes mellitus with blood sugar levels in type 2 diabetes mellitus patients at Dr. H. Abdul Moeloek Regional General Hospital in Lampung Province. This study used a descriptive method with a cross-sectional study design. Sampling was conducted using non-probability sampling, specifically consecutive sampling, with instruments in the form of questionnaires to measure knowledge levels and random blood sugar level tests. Data were analyzed using the chi-square test to see the relationship between variables. A total of 35 respondents participated in this study, with 11.4% in the good knowledge category, 14.3% in the adequate category, and 74.3% in the poor category. The average blood sugar level of the respondents was 285 mg/dL. The statistical test results showed a p-value of 0.003, indicating a significant difference between the level of knowledge about diabetes mellitus and fasting blood sugar levels. Thus, this study concluded that the level of patient knowledge has a significant relationship with fasting blood sugar levels in type 2 DM patients.